HIF‐1α induction, proliferation and glycolysis of Theileria‐infected leukocytes. (26th February 2015) - Metheni, Mehdi; Lombès, Anne; Bouillaud, Frédéric; Batteux, Frédéric; Langsley, Gordon
Summary Within 2 h of infection by Theileria annulata sporozoites, bovine macrophages display a two‐ to fourfold increase in transcription of hypoxia inducible factor (HIF‐1α). Twenty hours post‐invasion sporozoites develop into multi‐nucleated macroschizonts that transform the infected macrophage into an immortalized, permanently proliferating, hyper‐invasive and disease‐causing leukaemia‐like cell. Once immortalized Theileria‐infected leukocytes can be propagated as cell lines and even though cultivated under normoxic conditions, both infected B cells and macrophages display sustained activation of HIF‐1α. Attenuated macrophages used as live vaccines against tropical theileriosis also display HIF‐1α activation even though they have lost their tumorigenic phenotype. Here, we review data that ascribes HIF‐1α activation to the proliferation status of the infected leukocyte and discuss the possibility that Theileria may have lost its ability to render its host macrophage virulent due to continuous parasite replication in a high Reactive Oxygen Species (ROS) environment. We propose a model where uninfected macrophages have low levels of H2O2 output, whereas virulent‐infected macrophages produce high amounts of H2O2. Further increase in H2O2 output leads to dampening of infected macrophage virulence, a characteristic of disease‐resistant macrophages. At the same time exposure to H2O2 sustains HIF‐1α that induces the switch from mitochondrial oxidative phosphorylation to Warburg glycolysis, a metabolic shift that underpins uncontrolled infected macrophage proliferation. We propose that as macroschizonts develop into merozoites and infected macrophage proliferation arrests, HIF‐1α levels will decrease and glycolysis will switch back from Warburg to oxidative glycolysis. As Theileria infection transforms its host leukocyte into an aggressive leukaemic‐like cell, we propose that manipulating ROS levels, HIF‐1α induction and oxidative over Warburg glycolysis could contribute to improved disease control. Finally, as excess amounts of H2O2 drive virulent Theileria‐infected macrophages towards attenuation it highlights how infection‐induced pathology and redox balance are intimately linked.